2021
DOI: 10.3390/molecules26237115
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid and Diabetes Mellitus: Its Association with Oxidative Stress

Abstract: Diabetes mellitus (DM) is a severe chronic metabolic disease with increased mortality and morbidity. The pathological progression of DM is intimately connected with the formation and activation of oxidative stress (OS). Especially, the involvement of OS with hyperglycemia, insulin resistance, and inflammation has shown a vital role in the pathophysiological development of DM and related complications. Interestingly, accumulating studies have focused on the exploration of natural antioxidants for their improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 87 publications
1
43
0
6
Order By: Relevance
“…Gallic acid is a phenolic acid widely distributed in many different families of higher plants with high antioxidant properties. Gallic acid can improve high glucose levels, insulin, inflammation, and oxidative stress in diabetic complications by activating multiple effective pathways such as NO/iNOS generation, AGE/ALE, and JNK/ERK [ 28 ]. The anti-inflammatory mechanism of gallic acid mainly involves the MAPK and NF-kappa B signalling pathways, which attenuate the inflammatory response by reducing the release of inflammatory cytokines, chemokines, adhesion molecules, and cellular infiltration [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallic acid is a phenolic acid widely distributed in many different families of higher plants with high antioxidant properties. Gallic acid can improve high glucose levels, insulin, inflammation, and oxidative stress in diabetic complications by activating multiple effective pathways such as NO/iNOS generation, AGE/ALE, and JNK/ERK [ 28 ]. The anti-inflammatory mechanism of gallic acid mainly involves the MAPK and NF-kappa B signalling pathways, which attenuate the inflammatory response by reducing the release of inflammatory cytokines, chemokines, adhesion molecules, and cellular infiltration [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid is a phenolic acid widely distributed in many different families of higher plants with high antioxidant properties. Gallic acid can improve high glucose levels, insulin, inflammation, and oxidative stress in diabetic complications by activating multiple effective pathways such as NO/iNOS generation, AGE/ALE, and JNK/ERK [28].…”
Section: Research On Key Activementioning
confidence: 99%
“…Of particular interest to our study, Villani et al [ 15 ] reported detectable levels of gallic acid in only 5 of 21 commercial grape seed supplements that ranged from 11 to 102 mg/g in content. Gallic acid exhibits beneficial effects through anti-oxidant, anti-proliferative, and anti-inflammatory actions [ 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid (GA), which is found in a wide variety of fruits, nuts, and plants (e.g., rhubarb, eucalyptus, Cornus), is a polyphenol organic compound that is also known as 3,4,5-trihydroxy benzoic acid [ 29 , 30 ]. Its anti-inflammatory effects in various diseases have been demonstrated in many studies [ 31 ], for example, diabetes mellitus [ 32 ], psoriasis [ 33 ], gouty arthritis [ 34 ], paraquat-induced renal injury [ 35 ], etc. Gallic acid may prevent the production of inflammatory factors downstream of NF-κB, such as IL-1β, TNF-α, and thioredoxin-like protein-4B [ 36 ].…”
Section: Introductionmentioning
confidence: 99%